Prefrontal contributions to mental resilience: Lessons from rodent studies of stress and antidepressant actions - Ryota Shinohara; Tomoyuki Furuyashiki (Neuroscience Research)
Individual variability of stress susceptibility led to the concept of stress resilience to adapt well upon stressors. However, the neural mechanisms of stress resilience and its relevance to antidepressant actions remain elusive. In rodents, chronic stress induces dendritic atrophy and decreases dendritic spine density in the medial prefrontal cortex (mPFC), recapitulating prefrontal alterations in depressive patients, and the mPFC promotes stress resilience. Whereas dopamine neurons projecting to the nucleus accumbens potentiated by chronic stress promote stress susceptibility, dopamine neurons projecting to the mPFC activated upon acute stress contribute to dendritic growth of mPFC neurons via dopamine D1 receptors, leading to stress resilience. Rodent studies have also identified the roles of prefrontal D1 receptors as well as D1 receptor-expressing mPFC neurons projecting to multiple subcortical areas and dendritic spine formation in the mPFC for the sustained antidepressant-like effects of low-dose ketamine. Thus, understanding the cellular and neural-circuit mechanism of prefrontal D1 receptor actions paves the way for bridging the gap between stress resilience and the sustained antidepressant-like effects. The mechanistic understanding of stress resilience might be exploitable for developing antidepressants based on a naturally occurring mechanism, thus safer than low-dose ketamine.